“Licentious Barbarians”: representations of North African Muslims in Britain - Mohd Ramli, Aimillia (International Islamic University Malaysia, 2009)
This study traces the various historical contexts under which representations of North African Muslims were created from the sixteenth century until the nineteenth century in Britain. It shows that the image of Muslims that is being propagated in the media today as sexually licentious, oppressive towards women and barbaric were created from the earliest encounters between Westerners and Muslims from North Africa in the sixteenth century and became gradually consolidated in both fictional and factual writings throughout a few centuries up until the nineteenth century. While historical contexts experienced change as a result of the advent and decline of the Ottoman Empire as well as the emergence of Western Imperialism in the nineteenth century, images of Muslims remained largely the same.